Financial hardship and mental health among cancer survivors during the COVID-19 pandemic: An analysis of the US COVID-19 Household Impact Survey - Islam, Jessica Y.; Turner, Kea; Saeb, Huda; Powell, Margaux; Dean, Lorraine T.; Camacho-Rivera, Marlene (Frontiers in Public Health, 2022)
Purpose Our objective was to (1) identify associated characteristics of financial hardship (FH), and (2) evaluate associations of FH with mental health symptoms among cancer survivors during the COVID-19 pandemic. Methods Using data from the nationally representative COVID-19 Impact Survey, we defined cancer survivors as those with a self-reported diagnosis of cancer (n = 854,7.6%). We defined FH using the following question: “Based on your current financial situation, how would you pay for an unexpected $400 expense?” Multivariable Poisson regression was used to estimate adjusted prevalence ratios (aPR) with 95% confidence intervals (95%CI) to identify associated characteristics of FH and associations of FH with mental health symptoms among cancer survivors overall and by age (18–59 years/60+ years). Results Forty-one percent of cancer survivors reported FH, with 58% in 18–59 and 33% in 60+ year old respondents. Compared to cancer survivors aged 60+ years, those aged 30–44 (aPR:1.74,95% CI:1.35–2.24), and 45–59 years (aPR:1.60,95% CI:1.27–1.99) were more likely to report FH. Compared to non–Hispanic(NH)–White cancer survivors, NH–Black cancer survivors had a 56% higher prevalence of FH (aPR:1.56; 95% CI: 1.23–1.97). Among 60+ years aged cancer survivors, NH–Black (aPR:1.80; 95% CI: 1.32–2.45) and NH–Asian cancer survivors (aPR:10.70,95% CI:5.6–20.7) were more likely to experience FH compared to their NH–White counterparts. FH was associated with feeling anxious (aPR:1.51,95% CI:1.11–2.05), depressed (aPR:1.66,95% CI:1.25–2.22), and hopeless (aPR:1.84,95% CI:1.38–2.44). Conclusion Minoritized communities, younger adults, and cancer survivors with low socioeconomic status had a higher burden of FH, which was associated with feelings of anxiety, depression, and hopelessness.